THE EFFECT OF ENGLISH SUBTITLE IN â€œZOOTOPIAâ€ MOVIE IN SPEAKING SKILL - Megawati, Fhuri; Nuroh, Ermawati Z. (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2018)
This study investigated the effect of using English Subtitle in â€œZootopiaâ€ Movie as media in speaking skill of SMPN 6 Sidoarjo. English Subtitle can describe as practice media to help the students when they understand to watch movie. The method used Quasi Experimental Design. The result of this study showed that the student could improve their ability in speaking skill through English subtitle. The data got from both pre-test and post-test score were analyzed using T-test formula. The result of calculation showed that in the significance degree of 5%, the value of t-test (to) is higher than t-table (tt) (19.90 > 1.99). According to the criteria of the test, the result showed that there is an effect of studentâ€™s in speaking skill using English subtitle. It can be concluded that English Subtitle in â€œZootopiaâ€ movie as media is effective and applicable approach at the ninth grade of SMPN 6 Sidoarjo to improve student in speaking skill.